Combined Microencapsulated Islet Transplantation and Revascularization of Aortorenal Bypass in a Diabetic Nephropathy Rat Model - Yunqiang He; Ziqiang Xu; Hongxing Fu; Bin Chen; Silu Wang; Bicheng Chen; Mengtao Zhou; Yong Cai (Journal of Diabetes Research)
Objective. Revascularization of aortorenal bypass is a preferred technique for renal artery stenosis (RAS) in diabetic nephropathy (DN) patients. Restenosis of graft vessels also should be considered in patients lacking good control of blood glucose. In this study, we explored a combined strategy to prevent the recurrence of RAS in the DN rat model. Methods. A model of DN was established by intraperitoneal injection of streptozotocin. Rats were divided into 4 groups: SR group, MIT group, Com group, and the untreated group. The levels of blood glucose and urine protein were measured, and changes in renal pathology were observed. The expression of monocyte chemoattractant protein-1 (MCP-1) in graft vessels was assessed by immunohistochemical staining. Histopathological staining was performed to assess the pathological changes of glomeruli and tubules. Results. The levels of urine protein and the expression of MCP-1 in graft vessels were decreased after islet transplantation. The injury of glomerular basement membrane and podocytes was significantly ameliorated. Conclusions. The combined strategy of revascularization and microencapsulated islet transplantation had multiple protective effects on diabetic nephropathy, including preventing atherosclerosis in the graft vessels and alleviating injury to the glomerular filtration barrier. This combined strategy may be helpful for DN patients with RAS.